Penguatan Bisnis Melalui Pelatihan Pengelolaan Keuangan Berbasis Digital Bagi Pelaku UMKM Di Kecamatan Wangon - Alfalisyado; Yudhistira Pradhipta Aryoko; Firdaus; Meydy Fauziridwan (JCSE: Journal of Community Service and Empowerment, 2023)
The recipients of this service program are micro and small business actors who are members of KSPPS BMT Mentari Ummat Wangon. This activity was carried out to increase participants' knowledge and habituation regarding discipline in managing business finances with the ease of digital applications. This activity was conducted through counselling and training sessions for all participants offline. Some stages are pre-field observations, situation analysis and planning, preparation of places and equipment, program implementation (counselling, training, and mentoring), and monitoring and evaluation. The counselling and training materials provided were financial mindset, planning and budgeting, business financial management and training on using digital media in recording business transactions. The result of this program is that participants understand the importance of disciplined business financial management, even though it is done; besides, participants can operate digital applications for business financial management.